IMPLEMENTASI SERVICE LEARNING DALAM DESAIN INKLUSI DI SEKOLAH MENENGAH PERTAMA LUAR BIASA - A YAYASAN PENDIDIKAN ANAK-ANAK TUNA NETRA, (SMPLB-A YPAB), SURABAYA - Gunawan Tanuwidjaja (Institute of Research and Community Outreach - Petra Christian University, 2013)
Special Junior High School of Educational Foundation for the Blind Children (SMPLB-A YPAB), in Jalan Gebang Putih No.5 Surabaya, was a special school for diffable students for years. Unfortunately the school was less accessible. Therefore an accessibility evaluation and participatory design were needed for answering this challenge. The evaluation and design were conducted in a framework of Service Learning AR.633 Inclusive Design Course conducted by the Architectural Program if Petra Christian University. The Service Learning method was suitable for this because educating the architectural students about the Inclusive Design and serving the less privilege persons such as diffable students. The evaluation process as well as participatory or inclusive design was creative. The process involved the interview with blind students and blind teachers, the accessibility simulation of the Architectural students in the blind school, the Focus Group Discussions with diffable students and teachers (including the diffable teachers). The 1:20 - scale - architectural - model was found effective for the communi-cation process. And, two alternative designs were proposed for renovating the blind school. The case emphasized that creative process need more participation of all stakeholders in the building.